Improving the experiment report writing skills of fifth graders through the discovery learning method - Rita Indriyanti; Zuhdan Kun Prasetyo (Asosiasi Dosen PGSD dan Dikdas Indonesia, 2018)
This study aimed to improve the experimental report writing skills through the discovery learning method of the fifth graders of Muhammadiyah Sapen Elementary School Yogyakarta. This study was classroom action research. The subjects were 26 students of the fifth grade. The techniques for collecting data were observation, task, and documentation. The instruments of the data collection were observation sheets and writing performance. The result of this study showed that the process approach with the discovery learning method could improve the experimental report writing skills of the fifth-grade students of Muhammadiyah Sapen Elementary School Yogyakarta. It could be seen from the result of students’ observation sheet and writing performance. The observation result indicated the increase of the process and result of experimental report writing skills with the average score of 74.88 in Cycle I to 89.38 in Cycle II. The percentage of the Minimum Criteria for Mastery Learning in Cycle I was 60% and increased to 96% in Cycle II, with 24 the students achieved the mastery level and one failed. This showed that the students’ classical mastery was achieved.